2001
DOI: 10.1079/bjn2000220
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of LDL to oxidative modification in healthy volunteers supplemented with low doses ofn-3 polyunsaturated fatty acids

Abstract: The objective of the present study was to evaluate the oxidative susceptibility of LDL in human volunteers following supplementation with various low doses (<1 g/d) ofn–3 polyunsaturated fatty acids (PUFA). Sixty-two healthy volunteers (thirty-seven males and twenty-five females, aged 19–63 years) were recruited to take part in a randomised placebo-controlled trial. Volunteers were required to take 0.9, 0.6 or 0.3 gn–3 PUFA as fish oil or placebo capsules daily for 16 weeks. Susceptibility of LDL to oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 46 publications
3
22
1
Order By: Relevance
“…However, studies addressing this question have demonstrated conflicting results. In some studies, LDL particles showed an enhanced susceptibility to oxidation after intake of EPA and DHA (Oostenbrug et al, 1994;Suzukawa et al, 1995;Turini et al, 2001), whereas other studies revealed no such effect (Frankel et al, 1994;Bonanome et al, 1996;Wander et al, 1996;Higdon et al, 2001;Higgins et al, 2001). These contradictory findings may be related to methodical differences in the assays used for measuring LDL oxidation.…”
Section: Introductioncontrasting
confidence: 38%
“…However, studies addressing this question have demonstrated conflicting results. In some studies, LDL particles showed an enhanced susceptibility to oxidation after intake of EPA and DHA (Oostenbrug et al, 1994;Suzukawa et al, 1995;Turini et al, 2001), whereas other studies revealed no such effect (Frankel et al, 1994;Bonanome et al, 1996;Wander et al, 1996;Higdon et al, 2001;Higgins et al, 2001). These contradictory findings may be related to methodical differences in the assays used for measuring LDL oxidation.…”
Section: Introductioncontrasting
confidence: 38%
“…Concerns have been raised about the oxidative stress that can result from increased intakes of n-3 polyunsaturated fatty acids (Kris-Etherton et al, 2000;Sanders, 2000). There are some studies in humans concerning lipid peroxidation in plasma or LDL after intake of fish oils, using both high (Higdon et al, 2000(Higdon et al, , 2001 and low doses of fish oil (Higgins et al, 2001). None of these studies found an increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is concern that the LDL produced in the context of a high LC n-3 PUFA intake may be more vulnerable to oxidation, given its increased PUFA content. Conflicting evidence exists regarding the 'oxidisability' of LDL following LC n-3 PUFA consumption (Higgins et al 2001;Finnegan et al 2003). However, it has been suggested that the benefits of LC n-3 PUFA may be offset to some extent by increased oxidation of LDL within the arterial intima and consequent increased inflammatory processes.…”
Section: Mechanisms Of Cardioprotectionmentioning
confidence: 99%